Pulse Waveform Analysis of the Ocular Blood Flow Using Laser Speckle Flowgraphy before and after Glaucoma Treatment - Satoko Masai; Kyoko Ishida; Ayako Anraku; Tetsuro Takumi; Goji Tomita (Journal of Ophthalmology)
Although reduction in intraocular pressure (IOP) is the principle of glaucoma treatment, impaired ocular blood flow is believed to play a role in the progression of glaucoma. This study evaluated the effect of glaucoma treatment on pulse waveforms for optic nerve head (ONH) microcirculation in patients with glaucoma. Fifty-one subjects were included on the basis of the glaucoma treatment administered, which involved instillation of prostaglandin (PG) analogs (PG group; n = 28) or trabeculectomy (trabeculectomy group; n = 23). ONH blood flow, represented by the mean blur rate (MBRT) and pulse waveforms, was measured using laser speckle flowgraphy before and 1 and 3 months after treatment. Three months after treatment, IOP exhibited a significant decrease (p<0.05). Although there was no significant change in MBRT after treatment, the acceleration time index (ATI) significantly decreased (p=0.034) in the PG group. In the trabeculectomy group, there was no significant change in the MBRT after treatment, while fluctuation (p=0.019) and blowout score (BOS) (p=0.036) exhibited significant decrease and increase, respectively. Multiple regression analysis showed that mean deviation was significantly associated with the rate of change in the BOS (p=0.013), age was a significant contributing factor for the rate of change in fluctuation in the trabeculectomy group, reflection was significantly associated with the ATI (p=0.037) in the in the PG group. Both glaucoma treatments can change the pulse waveforms, with MBRT remaining unchanged, and IOP reduction owing to the treatment may contribute to stable blood flow in the tissue area of the ONH. As impaired ocular blood flow plays a role in the progression of glaucomatous damage, it would be beneficial if glaucoma treatment could improve the stability of ONH microcirculation.